Ubiquitin-activating enzyme UBA1 is required for cellular response to DNA damage - Moudry, Pavel; Lukas, Claudia; Macurek, Libor; Hanzlikova, Hana; Hodny, Zdenek; Lukas, Jiri; Bartek, Jiri (Cell cycle (Georgetown, Tex.), 2012)
The cellular DNA damage response (DDR) machinery that maintains genomic integrity and prevents severe pathologies, including cancer, is orchestrated by signaling through protein modifications. Protein ubiquitylation regulates repair of DNA double-strand breaks (DSBs), toxic lesions caused by various metabolic as well as environmental insults such as ionizing radiation (IR). Whereas several components of the DSB-evoked ubiquitylation cascade have been identified, including RNF168 and BRCA1 ubiquitin ligases, whose genetic defects predispose to a syndrome mimicking ataxia-telangiectasia and cancer, respectively, the identity of the apical E1 enzyme involved in DDR has not been established. Here, we identify ubiquitin-activating enzyme UBA1 as the E1 enzyme required for responses to IR and replication stress in human cells. We show that siRNA-mediated knockdown of UBA1, but not of another UBA family member UBA6, impaired formation of both ubiquitin conjugates at the sites of DNA damage and IR-induced foci (IRIF) by the downstream components of the DSB response pathway, 53BP1 and BRCA1. Furthermore, chemical inhibition of UBA1 prevented IRIF formation and severely impaired DSB repair and formation of 53BP1 bodies in G 1, a marker of response to replication stress. In contrast, the upstream steps of DSB response, such as phosphorylation of histone H2AX and recruitment of MDC1, remained unaffected by UBA1 depletion. Overall, our data establish UBA1 as the apical enzyme critical for ubiquitylation-dependent signaling of both DSBs and replication stress in human cells, with implications for maintenance of genomic integrity, disease pathogenesis and cancer treatment.
Keywords: RNA interference; 53BP1; intracelulární signální peptidy a proteiny; Radiation, Ionizing; Cell Nucleus; Cell Line, Tumor; G1 fáze; ionizující záření; Tumor Suppressor p53-Binding Protein 1; Pyrazoles; Intracellular Signaling Peptides and Proteins; furany; buněčné jádro; ubikvitin aktivující enzymy; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; Ubiquitin-Activating Enzymes; Ubiquitination; ubikvitinace; benzoáty; RNA, Small Interfering; DNA Repair; RNA Interference; oprava DNA; lidé; Humans; malá interferující RNA; Benzoates; G1 Phase; nádorové buněčné linie; pyrazoly; Furans